Robert C. Brickell, Commissioner, The Code of Alabama, Adopted by Act of the General Assembly Approved February 28, 1887; with Such Statutes Passed at the Session of 1886-87, as are Required to Be Incorporated Therein by Act Approved February 21, 1887; and with Citations of the Decisions of the Supreme Court of the State Construing the Statutes Page 93 § 4093 - (:unkn) unknown (General Publisher, 1887)
Prohibited storage of gun powder exceeding fifty pounds within any incorporate city or town. Violators fined not less than one hundred dollars.
--
Keywords: GUN POWDER STORAGE